Prominence and Engagement: Different Mechanisms Regulating Continuance and Contribution in Online Communities - Kuem, Jungwon; Khansa, Lara; Kim, Sung S. (Journal of Management Information Systems, 2020)
Online communities have suffered from their members’ intermittent, dormant, or nonexistent participation. We propose that prominence, which refers to the salience of community members’ psychological proximity to their community, differs from the engagement construct, which denotes a psychological dedication to behave prosaically toward other community members. Whereas engagement has been increasingly examined as a driver of online community behavior, the role of prominence has received a minimal amount of attention in the literature. Drawing on self-determination theory, we developed a framework that proposes the prominence construct as a phenomenon distinctive from engagement in its nature, formation, and behavioral outcomes. Our findings based on two studies indicate that the proposed model with prominence performs considerably better than the existing model with only engagement. Our conceptual model contributes to Information Systems research by laying a strong theoretical foundation to differentiate between the behavioral paths of the autonomous prominence construct and its controlled engagement counterpart.